Effect of evolution of the C‐terminal region on chaperone activity of Hsp70. (29th December 2022) - Zhang, Hong; Hu, Huimin; Wu, Si; Perrett, Sarah
Abstract: Dynamic interdomain interactions within the Hsp70 protein is the basis for the allosteric and functional properties of Hsp70s. While Hsp70s are generally conserved in terms of structure, allosteric behavior, and some overlapping functions, Hsp70s also contain variable sequence regions which are related to distinct functions. In the Hsp70 sequence, the part with the greatest sequence variation is the C‐terminal α‐helical lid subdomain of substrate‐binding domain (SBDα) together with the intrinsically disordered region. Dynamic interactions between the SBDα and β‐sandwich substrate‐binding subdomain (SBDβ) contribute to the chaperone functions of Hsp70s by tuning kinetics of substrate binding. To investigate how the C‐terminal region of Hsp70 has evolved from prokaryotic to eukaryotic organisms, we tested whether this region can be exchanged among different Hsp70 members to support basic chaperone functions. We found that this region from eukaryotic Hsp70 members cannot substitute for the same region in Escherichia coli DnaK to facilitate normal chaperone activity of DnaK. In contrast, this region from E. coli DnaK and Saccharomyces cerevisiae Hsp70 (Ssa1 and Ssa4) can partially support some roles of human stress inducible Hsp70 (hHsp70) and human cognate Hsp70 (hHsc70). Our results indicate that the C‐terminal region from eukaryotic Hsp70 members cannot properly support SBDα–SBDβ interactions in DnaK, but this region from DnaK/Ssa1/Ssa4 can still form some SBDα–SBDβ interactions in hHsp70 or hHsc70, which suggests that the mode for SBDα–SBDβ interactions is different in prokaryotic and eukaryotic Hsp70 members. This study provides new insight in the divergency among different Hsp70 homologs and the evolution of Hsp70s.